85.3k views
5 votes
(-8) - (-11) x [(-2) - {(-8)+(-11)}]

NEED ANSWER ASAP

2 Answers

6 votes

Answer:

179.

Explanation:

Use order of operations (PEMDAS).

First work out the 'inner' parentheses, then the outer ones:

(-8) - (-11) x [(-2) - {(-8)+(-11)}]

= (-8) - (-11) x [(-2) - {-19}]

= (-8) - (-11) x [17]

= -8 - (-11 * 17)

Now perform the multiplication:

= -8 - (-187)

= 179 (answer).

User Rawa
by
5.9k points
2 votes
remember your order of operations so begin with the smaller parentheses in the larger one, then the larger parentheses, then the multiplication and finally the subtraction
(-8) - (-11) x [(-2) - {(-8)+(-11)}] NEED ANSWER ASAP-example-1
User Effkay
by
6.2k points